2007
DOI: 10.1007/s11146-007-9067-1
|View full text |Cite
|
Sign up to set email alerts
|

Boom–Bust Cycles and the Forecasting Performance of Linear and Non-Linear Models of House Prices

Abstract: Bubbles, Forecasting models, Generalized autoregressive model, Nonlinear techniques,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 20 publications
1
57
1
Order By: Relevance
“…Moreover, we also examine this issue of the forecast performance of non-linear versus linear models for interval and density forecasts, in addition to point forecasts. Miles (2008) considers linear and nonlinear forecasts of house prices in five US states -California, Florida, Massachusetts, Ohio, and Texas -using the generalized autoregressive (GAR) model. He concludes that the "GAR does a better job at out-of-sample forecasting … in many cases, especially in those markets traditionally associated with high home-price volatility."…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we also examine this issue of the forecast performance of non-linear versus linear models for interval and density forecasts, in addition to point forecasts. Miles (2008) considers linear and nonlinear forecasts of house prices in five US states -California, Florida, Massachusetts, Ohio, and Texas -using the generalized autoregressive (GAR) model. He concludes that the "GAR does a better job at out-of-sample forecasting … in many cases, especially in those markets traditionally associated with high home-price volatility."…”
Section: Introductionmentioning
confidence: 99%
“…Mills (2008) showed that housing business is a critical factor in a close relation to a country's economy from the viewpoint of policy-making authorities, citing that 20 housing business recessions between 1970 and 2000 led to 19 economic recessions in OECD countries. Crawford (1995) showed that housing price volatility is a major factor behind mortgage default and loan prepayment, and is particularly very important to financial institutions heavily relying on housing mortgage loans.…”
Section: Background Of Studymentioning
confidence: 99%
“…Ou Tinghao (2007) W. Miles (2008) proves that the GAM model surpasses ARMA and the GARCH model in the forecast aspect when analyzing house price which is nonlinear system through experiment. Particularly, its application has better effect in the high price tradition housing market which is in existence of soaks the desert.…”
Section: Regression Time Series Stochastic Process and Fuzzymentioning
confidence: 99%